2012
DOI: 10.1002/ijc.27791
|View full text |Cite
|
Sign up to set email alerts
|

Circulating U2 small nuclear RNA fragments as a novel diagnostic biomarker for pancreatic and colorectal adenocarcinoma

Abstract: Improved non-invasive strategies for early cancer detection are urgently needed to reduce morbidity and mortality. Non-coding RNAs, such as microRNAs and small nucleolar RNAs, have been proposed as biomarkers for non-invasive cancer diagnosis. Analyzing serum derived from nude mice implanted with primary human pancreatic ductal adenocarcinoma (PDAC), we identified 15 diagnostic microRNA candidates. Of those miR-1246 was selected based on its high abundance in serum of tumor carrying mice. Subsequently, we note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 44 publications
9
106
1
Order By: Relevance
“…Previous reports have shown that the Qiagen miR-1246 assay, when used for lysates of tumor cell lines, produces an amplicon of approximately 180 bp in size, corresponding to full-length RNU2-1 and not to its fragmented counterpart found in human serum (RNU2-1f) (16 ). We could confirm the formation of a 180-bp amplicon by this assay, when applied to ovarian cancer tissue (data not shown).…”
Section: Full-length Rnu2-1 Expression In Ovarian Cancer Tissuesupporting
confidence: 72%
See 3 more Smart Citations
“…Previous reports have shown that the Qiagen miR-1246 assay, when used for lysates of tumor cell lines, produces an amplicon of approximately 180 bp in size, corresponding to full-length RNU2-1 and not to its fragmented counterpart found in human serum (RNU2-1f) (16 ). We could confirm the formation of a 180-bp amplicon by this assay, when applied to ovarian cancer tissue (data not shown).…”
Section: Full-length Rnu2-1 Expression In Ovarian Cancer Tissuesupporting
confidence: 72%
“…Absence of syn-cel-miR-54 signal in the human circulation was experimentally verified previously (9 ), and a previous investigation showed a linear correlation between the logarithm of the amount of syn-celmiR-54 input and the Cq for syn-cel-miR-54 as well as RNU2-1f (16 ). From these analyses, we verified the adjusted amount of spike-in (25 fmol per sample) to be in the linear amplification range of the assay (16 ). We determined a normalized Cq value for RNU2-1f relative to the syn-cel-miR-54 signal [Cq ϭ Cq(syn-celmiR-54) Ϫ Cq(RNU2-1f)].…”
Section: Rt-qpcrsupporting
confidence: 69%
See 2 more Smart Citations
“…We evaluated the expression of plasma miRs using the S-Poly (T) reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) method as previously described (Kang et al 2012), using miR-54 as a control (Baraniskin et al 2013;Huang et al 2016). The comparative cycle threshold (Ct) (ΔCt) was used to calculate the relative expression level of miRs.…”
Section: The Measurement Of Plasma Mir-29a and Apnmentioning
confidence: 99%